African farmers’ market organizations and global value chains: Competitiveness versus inclusiveness - Lutz, Clemens; Tadesse, Getaw (Informa UK Limited, 2017)
This conceptual paper discusses the challenges smallholder producer cooperatives in developing countries face while trying to access agricultural global value chains. We assess the problem of competitiveness related to lack of commitment and improper selection. Prioritization of open membership over selection is generally taken for granted in the policy debate on farmers’ market organizations (FMOs). We argue that open membership may work in community-driven organizations, however, it becomes a major threat for entrepreneurial FMOs. Inclusion facilitates free riding, which forms a barrier for investments of members. This is one of the major reasons why so many of these organizations are so much resource constrained, i.e. are not able to compete in the market without external support. FMOs should take targeting and selection serious if entrepreneurial activities are intended. Otherwise, they miss the opportunity to create a committed member base willing to invest in a potentially competitive organization.